Bioreactor Scale-Up and Kinetic Modeling of Lactic Acid and Biomass Production by Enterococcus faecalis SLT13 during Batch Culture on Hydrolyzed Cheese Whey. (9th March 2020) - Ziadi, Manel; M'Hir, Sana; Aydi, Abdelkarim; Hamdi, Moktar
Abstract : Kinetic modeling of biomass and lactic acid production by Enterococcus faecalis SLT13 have been developed during batch culture in M17 and Hydrolyzed Cheese Whey (HCW) in 2 L and 20 L bioreactors. The specific growth rate μ max was higher in 20 L bioreactor (1.09 h −1 ); however, the maximum specific lactic acid production rate q p max and maximum specific sugar utilization rate q s max were higher in 2 L bioreactor. Biomass and sugar utilization were affected by lactic acid inhibition in HCW. No effects of substrate inhibition have been observed. Substrate limitation of biomass has been observed on HCW in 20 L bioreactor; the substrate limitation constant for biomass K sx was 4.229 g/L. Substrate limitation of sugar consumption has been observed on M17 in 2 L bioreactor; the substrate limitation constant for sugar consumption K ss was 2.73 g/L. Compared to experimental data, the model provided good predictions for biomass, sugar consumption, and lactic acid production.